Pulpability Of Oil Palm Empty Fruit Bunch Via Alkaline Peroxide Treatment - Yusoff, Rosnah Muhd (2011)

(untitled)
The effects of alkaline peroxide (AP) concentration level and pre-treatment time on oil palm empty fruit bunch (EFB) were studied. The impregnation of EFB with alkaline peroxide was observed at three levels of alkaline peroxide concentration, which were categorized as high (5% H2O2: 4% NaOH), medium (2.5% H2O2: 2%NaOH) and low (1.5% H2O2: 1% NaOH). The reaction was also observed at various pre-treatment time which were 0 minute, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes and 120 minutes.